Investigation of vibriosis caused by Vibrio anguillarum in rainbow trout (Oncorhynchus mykiss): Vibriosis caused by Vibrio anguillarum - Urku, Cigdem; Secer, Faik Sertel; Onalan, Sukru; Akayli, Tulay (Cellular and Molecular Biology, 2024)
Identifying pathogenic microorganisms causing disease is important for epidemiological research, antimicrobial therapy, and control. The current study was carried out to use different methods for the identification of Vibrio anguillarum from diseased rainbow trout (Oncorhynchus mykiss) obtained from Türkiye (Muğla-Fethiye), the damage caused by the pathogenic microorganism in the tissues and organs, and the determination of the antibiotic effective against the pathogen. Hemorrhagic and ulcerative skin lesions and diffuse petechial hemorrhage in the internal organs were clinically detected in diseased fish obtained from the rainbow trout farm. Bacteria isolated from diseased fish were subjected to analysis using conventional bacteriological methods, a commercial bacterial identification test kit (API), an automated bacteria identification system known as Matrix-Assisted Laser Desorption/Ionization Time-of-Flight Mass Spectrometry (MALDI-TOF MS), BD Phoenix™, and 16S rRNA sequence analysis. All isolated bacteria were identified as V. anguillarum by API 20E and conventional bacteriological method. These results have been confirmed with 16S rRNA sequence analysis. However, the isolated bacteria were identified as Grimontia hollisae (syn. Vibrio holisae) with the BD Phoenix system. Histologically, tissue damage such as melano-macrophage centers and necrosis in the kidney and spleen, hyperemia and mononuclear cell infiltration in the liver, as well as mononuclear cell infiltration on muscles, talengectiasis in the gill tissue was observed. In addition, it has been determined that the most effective antibiotic against the pathogen was enrofloxacin. When comparing all identification methods used for this pathogen causing tissue damage, it was demonstrated that the MALDI-TOF MS provides better results than other methods in terms of cost and identification time, and it could be used as an alternative to the conventional method to the identification of V. anguillarum.